2019
DOI: 10.12669/pjms.35.6.930
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and antibiogram of multi-drug resistant pseudomonas aeruginosa in a Tertiary Care Hospital of Pakistan

Abstract: Objective:To determine pathogen burden and susceptibility pattern of multi-drug resistant (MDR) Pseudomonas aeruginosa isolates from clinical specimens in Karachi.Methods:It was In-vitro Clinical study, conducted in department of Pharmacology, Ziauddin University, and isolates were collected from various specimens such as pus, tracheal aspiration, wound swab, blood and urine in Microbiology department of Ziauddin Hospital, Nazimabad campus, Karachi. The antibiotic susceptibility pattern was determined by Kirby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Another study conducted in Egypt showed highest incidence of P.aeruginosa at the burns unit as well as in ICU (Mahmoud, Zahran, Hindawi, Labib, & Galal, 2013). Another high frequency was also noted in Egypt (56%) (Farooq, Memon, Ismail, & Sadiq, 2019).…”
Section: Resultsmentioning
confidence: 88%
“…Another study conducted in Egypt showed highest incidence of P.aeruginosa at the burns unit as well as in ICU (Mahmoud, Zahran, Hindawi, Labib, & Galal, 2013). Another high frequency was also noted in Egypt (56%) (Farooq, Memon, Ismail, & Sadiq, 2019).…”
Section: Resultsmentioning
confidence: 88%
“…A total of fifteen articles published in English, between the period of 2010 and 2020 were identified and reviewed, nine articles were prospective studies (Siddiqua et al, 2018;Farooq et al, 2019;Ahmadi et al, 2016;Rustini et al, 2017;Senthamarai, 2014;Farhan et al, 2019;Ahmed et al, 2019;Al-Marzoqi and Al Taee, 2013;Khan and Faiz, 2016), four were descriptive cross sectional studies (Pokharel et al, 2019;Karami et al, 2020;Mahfoud et al, 2015;Alhusseini et al, 2019), one systemic review and meta-analysis study (Acar et al, 2019) and one retrospective study (Al-Tawfiq et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In Nepal MDRPA prevalence was reported according to the type of specimen where it found to be the highest in tracheal aspirate specimens (100%) and the lowest in pleural fluid samples (0%) (Pokharel et al, 2019). Female to male ratio for MDRPA prevalence was reported in two of the included articles as it was (1.17:1) in Pakistan (Farooq et al, 2019) and (1:3) in Qatar (Ahmed et al, 2019). Further information was reported in Pakistan regarding distribution of MDRPA according to medical ward as it was the highest in surgical ward (27.1%) and the lowest in the gynecology ward (4.1%) (Farooq et al, 2019).…”
Section: Mdrpamentioning
confidence: 97%
See 1 more Smart Citation
“…Microbial genomics and metagenomics played a key role in the identification of these MDR microbes which helped in designing effective strategies to mitigate or manipulate resistant microbes [ 12 ]. The high prevalence of MDR infections in Pakistan has been evidenced by numerous reports [ 13 ].…”
Section: Discussionmentioning
confidence: 99%